2010
DOI: 10.1158/1940-6207.capr-09-0254
|View full text |Cite
|
Sign up to set email alerts
|

Optical Measurement of Rectal Microvasculature as an Adjunct to Flexible Sigmoidosocopy: Gender-Specific Implications

Abstract: Flexible sigmoidoscopy is a robust, clinically-validated and widely available colorectal cancer (CRC) screening technique that is currently sanctioned by both major guideline organizations. Given that endoscopic visualization is generally limited to the distal third of the colon and women tend to have a proclivity for proximal lesions, flexible sigmoidoscopy’s performance is markedly inferior in women than men. Our group has demonstrated that by using a novel light scattering approach we were able to detect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The increased FASN in males versus females suggests that this colonic neoplasia biomarker may have a significant gender predilection. There is precedence for significant gender based biomarker specificity as can be seen in serum (C-reactive protein) [27] as well as from field carcinogenesis data (biophotonically derived or advanced adenomas) [28]. …”
Section: Discussionmentioning
confidence: 99%
“…The increased FASN in males versus females suggests that this colonic neoplasia biomarker may have a significant gender predilection. There is precedence for significant gender based biomarker specificity as can be seen in serum (C-reactive protein) [27] as well as from field carcinogenesis data (biophotonically derived or advanced adenomas) [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, developing a minimally intrusive pre-screening technique could substantially undermine the need for colonoscopy. We have published in situ data from over 700 subjects that confirms the promise of this approach (for advanced adenomas the area under the receiver operator curve was ~0.90)[14,35]. We envision simplifying our probes to the extent that they could be used at the primary care physician's office during annual rectal examination to effectively risk-stratify the population for colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We then demonstrated EIBS clinically using developed an endoscopically-compatible 4D-ELF fiber-optic probe in patients undergoing colonoscopy (2). Importantly, EIBS was detectable in the visually normal rectum in patients harboring advanced adenomas elsewhere in the colon (3)[14], thus suggesting applications as a minimally-intrusive risk-stratification.…”
Section: Introductionmentioning
confidence: 99%
“…As outlined in Table 2, smoking and drinking history also did not have any confounding effect on L d ( P = 0.57 for current smokers and P = 0.99 for drinking). Similarly, male gender is a well-established risk factor for colonic neoplasia(32). However, ANCOVA analysis indicated that there was no significant confounding with gender ( P = 0.29 for L d ).…”
Section: Resultsmentioning
confidence: 99%